Pengaruh Pemahaman Informasi KB dan Tingkat Ekonomi Keluarga terhadap Pemilihan Pemakaian Alat Kontrasepsi di Provinsi Kalimantan Tengah - Chandra Anugrah Putra; Muhammad Jailani; Ummi Qudsiyah; Ade Salahuddin Permadi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
This study aims to determine the magnitude of the influence of understanding family planning information and the economic level of the family on the choice of contraceptive use in women of childbearing age in Province Central Kalimantan. The research design used was an explanatory research design with a quantitative approach to post-facto models. The study population was 587 women of childbearing age in Central Kalimantan province and the sampling technique used was the total sampling technique. The analysis technique uses multiple linear regression analysis techniques with a significant level (p) smaller or equal to 0.05 (p <0.05) and smaller or equal to 0.01 (p <0.01). The results showed that the direct effect between the understanding of family planning information on the choice of contraceptive use was significant (p <0.01), with a value of β = 1.989; p <0.05. At the family economic level, the choice of contraceptive use was significant (p <0.01), with a value of β = -,972; p <0.01. The conclusion of the first research is proven that understanding family planning information has a significant effect on the choice of contraceptive use in women of childbearing age in the province of Central Kalimantan, the second is proven that the family economic level has a significant effect on the choice of contraceptive use in women of childbearing age in the province of Central Kalimantan. Research Suggestions.